The Toxic Effect of Essential Oil from Waste Cinnamon (Cinnamomum burmanii (Nees & T. Nees) Blume.) Leaf to Control Helopeltis antonii Signoret in Cocoa Plants in Vitro - Puspita, Roza; Rahayu, Resti; Mairawita, Mairawita; Nasir, Nasril; Nurmansyah, Nurmansyah (Metamorfosa: Journal of Biological Sciences, 2019)
The toxic effect of essential oil from waste  cinnamon leaf ( Cinnamomum burmanii )  against pests of cocoa fruit Helopeltis antonii (Hemiptera; Miridae),  has been done in Green House , Research Station Spice and Medicinal Plants, Laing Solok, West Sumatra in April to May 2016. The experiment aimed to determine repellant and lethal  concentrations of essential oil from waste s cinnamon leaf ( C. burmanii ) for H. antonii . There were 5  treatments  arranged in Complately Randomized Design with 4 replications. The treatments tested were essentialoil concentration f  (0.05 ml/tube, 0.1 ml/tube, 0.2 ml/tube and 0.5 ml/tube) and control. The results showed that the effective repellent concentration were 0,05 ml/tube and 0,1 ml/tube which repelled   H. antonii  0,03 % . The effecive lethal concentration was  0,05 ml/tube which killed   H. antonii  57,50 %. Concentration used was  highly  toxic which killed l H. Antonii within  six hours so of the repellent nature was notobserved.